At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which function results in a horizontal compression of [tex]\( y = \frac{1}{x} \)[/tex] by a factor of 6, let us review what horizontal compression means.
1. Understanding Horizontal Compression:
- To horizontally compress a function by a factor of [tex]\( k \)[/tex], you replace [tex]\( x \)[/tex] in the original function [tex]\( f(x) \)[/tex] with [tex]\( \frac{x}{k} \)[/tex].
- For example, if [tex]\( f(x) = \frac{1}{x} \)[/tex] and you want to horizontally compress it by a factor of 6, you would replace [tex]\( x \)[/tex] with [tex]\( \frac{x}{6} \)[/tex].
2. Applying Horizontal Compression:
- Start with the original function: [tex]\( y = \frac{1}{x} \)[/tex].
- Compress horizontally by a factor of 6 by replacing [tex]\( x \)[/tex] with [tex]\( \frac{x}{6} \)[/tex]:
[tex]\[ y = \frac{1}{\frac{x}{6}} \][/tex]
3. Simplifying the Function:
- Simplify [tex]\( \frac{1}{\frac{x}{6}} \)[/tex]:
[tex]\[ y = \frac{1}{\frac{x}{6}} = \frac{1 \cdot 6}{x} = \frac{6}{x} \][/tex]
Thus, the function [tex]\( y = \frac{6}{x} \)[/tex] is the result of a horizontal compression of [tex]\( y = \frac{1}{x} \)[/tex] by a factor of 6.
Comparing this to the options:
- [tex]\( y = \frac{1}{6x} \)[/tex] is incorrect as it represents a horizontal stretch.
- [tex]\( y = -\frac{1}{6x} \)[/tex] is incorrect as it also represents a stretch and a reflection.
- [tex]\( y = \frac{6}{x} \)[/tex] is correct.
- [tex]\( y = -\frac{6}{x} \)[/tex] is incorrect as it includes an additional reflection.
Therefore, the correct option is:
[tex]\[ \boxed{y = \frac{6}{x}} \][/tex]
This corresponds to option 3.
1. Understanding Horizontal Compression:
- To horizontally compress a function by a factor of [tex]\( k \)[/tex], you replace [tex]\( x \)[/tex] in the original function [tex]\( f(x) \)[/tex] with [tex]\( \frac{x}{k} \)[/tex].
- For example, if [tex]\( f(x) = \frac{1}{x} \)[/tex] and you want to horizontally compress it by a factor of 6, you would replace [tex]\( x \)[/tex] with [tex]\( \frac{x}{6} \)[/tex].
2. Applying Horizontal Compression:
- Start with the original function: [tex]\( y = \frac{1}{x} \)[/tex].
- Compress horizontally by a factor of 6 by replacing [tex]\( x \)[/tex] with [tex]\( \frac{x}{6} \)[/tex]:
[tex]\[ y = \frac{1}{\frac{x}{6}} \][/tex]
3. Simplifying the Function:
- Simplify [tex]\( \frac{1}{\frac{x}{6}} \)[/tex]:
[tex]\[ y = \frac{1}{\frac{x}{6}} = \frac{1 \cdot 6}{x} = \frac{6}{x} \][/tex]
Thus, the function [tex]\( y = \frac{6}{x} \)[/tex] is the result of a horizontal compression of [tex]\( y = \frac{1}{x} \)[/tex] by a factor of 6.
Comparing this to the options:
- [tex]\( y = \frac{1}{6x} \)[/tex] is incorrect as it represents a horizontal stretch.
- [tex]\( y = -\frac{1}{6x} \)[/tex] is incorrect as it also represents a stretch and a reflection.
- [tex]\( y = \frac{6}{x} \)[/tex] is correct.
- [tex]\( y = -\frac{6}{x} \)[/tex] is incorrect as it includes an additional reflection.
Therefore, the correct option is:
[tex]\[ \boxed{y = \frac{6}{x}} \][/tex]
This corresponds to option 3.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.